Optimal Power Improved Method For Induction Heating Application With High Resonant Boost Inverter - Selvam. P; Anandan. D (Journal of Power Electronics and Devices, 2019)
The induction heating is an primary work in many of the industrial applications and also it is used for medical products manufacturing units. This paper proposes an interleaved resonant boost inverter featuring single phase module to achieve high efficiency and performance IH power supply. By reducing the current of power switching device the efficiency of the converter can be increased by incorporating proposed technology. The current ripple can be reduced by implementing interleaved converter. The proposed converter can be tested by designing suitable control strategies. It is important to note the role and operation of the dclink capacitor in the proposed converter. From the point of view of the equivalent inverter side, the inverter can be modeled as a pure resistor if constant modulation parameters are applied. By combining this fact with the use of a small dc-link capacitor, a mains power factor close to the unit can be achieved. In the case of the proposed converter, a capacitor large enough to filter the high frequency harmonics but still providing a sinusoidal current consumption will be selected.